The implementation of in-service training for English as a foreign language teachers (EFL) in universities in Yinchuan - Wang, Yang (2018)
Previous studies showed that the in-service training for EFL teachers did not draw much attention at university level in China. The EFL teacher’s needs, the curriculum designs, the implement of reflective practice, and training activities were rarely considered in service training. Therefore, the purpose of this study is to determine the curriculum, reflective practice, and activities of in-service training, which are the predictors in-service training for EFL teachers as well as to investigate the teachers’ beliefs and the issues related to in-service training in universities in Yinchuan, China. In addition, mix-method approach was employed in this study. 128 EFL teachers were selected through a systematic sampling technique, using the on-line survey instrument in quantitative data collection; on the other hand, eight university’s EFL teachers were selected for interviews, using semi-structured questions in qualitative data collection. The results showed that the curriculum, reflective practice were the predictors of in-service training. Activities of in-service training was not the predictor of in-service training. It also found that in-service training should consider the needs of EFL teachers, focusing on subject and pedagogical content knowledge, transforming the traditional training into the reflective training way, and providing more training opportunities to EFL teachers. Interviewees showed that the key purpose of training was to build up the confidence of EFL teachers to teach English. The main issue was that no department was in charge of the in-service training in universities in Yinchuan. Finally, this study contributed to supporting Shuman’s theory of teacher knowledge and Wallace’s reflective practice as well as contributed to building the effectiveness of in-service training for EFL teachers in universities in Yinchuan, and providing new insights, using mix-method applied in this field.